Multi-Stage Recycling Induced Morphological Transformations in Solid-State Microcellular Foaming of Polystyrene. Issue 3 (May 2018) - Singh, Indrajeet; Gandhi, Abhishek; Biswal, Manoranjan; Mohanty, Smita; Nayak, S. K.
In this article, the general-purpose polystyrene was reprocessed four times. The effect of repeated reprocessing of polystyrene on its polymeric properties and on its microcellular, foaming behaviour were investigated. It was observed that reprocessing leads to break of long polymeric chains into short chains, which resulted increment in PDI and MFI. Molecular weight and Glass transition temperature were found to decrease with increasing recycling stages. Reprocessing resulted abruptly decrement in viscosity of neat polystyrene. Effect of reprocessing on foaming behaviour was analysed properly in this report and it was found that reprocessing resulted in improvement in cell sizes and their distribution. A positive effect on expansion ratio was also observed during foaming of reprocessed specimens. Cell density was found to decrease with increasing recycling stages. The effect of saturation pressure and foaming temperature on microcellular foam morphology along with recycling were investigated. Effect of foaming time on cell size, cell size distribution, cell density, expansion ratio and cell wall thickness was investigated.